057 The role of cytochrome p450 metabolites as an endothelium-derived hyperpolarising factor in the regulation of vascular tone in vivo in the forearm vasculature of healthy and diabetic individuals. (22nd September 2015) - Ozkor, M A; Murrow, J; Rahman, A; Kavtaradze, N; Arshad, S; Syed, H; Li, J; Manatunga, A; Quyyumi, A
Abstract : Background: Epoxyeicosatrienoic acids are arachidonic-acid-derived products of cytochrome P450 (CYP450) epoxygenases. Endothelium-derived hyperpolarizing factor (EDHF) stimulates calcium dependent potassium channels by CYP450 metabolites that can be inhibited with fluconazole (FLU). The role of EDHF in impaired endothelial function remains undefined. We hypothesised a differential contribution of EDHF in diabetics (DM) compared to healthy subjects. Methods: In 16 healthy and 14 DM subjects, we measured forearm blood flow (FBF) with venous occlusion strain gauge plethysmography at rest and after endothelium-dependent and -independent vasodilation with acetylcholine (7.5, 15, 30 μg/min) or bradykinin (100, 200, 400 ng/min) and sodium nitroprusside (1.6 and 3.2 μg/min), respectively. Measurements were repeated after NO blockade with LNG monomethyl arginine (L-NMMA, 8 μmol/min), CYP450 blockade with fluconazole (0.4–1.6 μmol/min) and combined NO and CYP450 blockade. Results: L-NMMA reduced resting FBF by −1.75 mls/min (p<0.05) in healthy subjects and −0.79 mls/min in DM (p<0.05). Fluconazole by itself reduced resting FBF by −0.52 mls/min, p=0.04 in DM, but not in healthy subjects (−0.28 mls/min, p=0.2), indicating an important contribution of CYP450 metabolites to resting vasodilator tone in DM. When Fluconazole was added to prior L-NMMA blockade, a further significant reduction of FBF was seen in healthy subjects (−1.06 mls/min, p=0.016), indicating a contribution of CYP450 metabolites to resting flow in healthy subjects only in the absence of NO. Acetylcholine and Bradykinin-mediated vasodilation was attenuated in DM. L-NMMA significantly inhibited Acetylcholine-mediated FBF in both groups with a trend towards a larger flow decrement in healthy than in DM subjects (−5.0 vs −2.3 mls/min, p=0.08) at peak Acetylcholine, indicating a decreased contribution of NO in DM. Fluconazole had no effect on Acetylcholine -mediated vasodilation alone or in addition to L-NMMA in either group. Similar trends were observed with Bradykinin-infusions. Sodium nitroprusside-mediated vasodilation was unchanged after L-NMMA and Fluconazole. Conclusions: NO is the major contributor to resting vasodilator tone in healthy subjects, whereas both NO and hyperpolarisation via CYP450 metabolites contribute to resting tone in DM. However, in the absence of NO in healthy subjects CYP450 metabolites were observed to have an important contribution suggesting an upregulation of EDHF activity via CYP450 metabolites when there is a decreased NO bioavailability. CYP450 metabolites do not contribute to pharmacologically stimulated vasodilation in either DM or healthy subjects, but whether other EDHFs play a role needs to be studied.